PRINSIP MASLAHAT AL-MURSALAH DALAM PRAKTIK PENGELOLAAN WAKAF PADA NAZHIR UNIVERSITAS AIRLANGGA - Thalib, Prawitra; Wisudanto, Wisudanto; Kurniawan, Faizal; Kholiq, Mohamad Nur (Universitas Brawijaya, 2023)
This paper aims tp discuss the legitimacy of AIW at Nazhir Airlangga University from the perspective of the waqf law and whether it has complied with the principle of maslahah mursalah, considering that various cases of waqf property do not run optimally, are productive, are not used or are transferred to third parties. There is an interesting phenomenon, namely that at Nazhir, Airlangga University is the only one and the first time an Indonesian State University has received a Nazhir certificate to manage and develop waqf. In this case, it is interesting to discuss the practice of waqf at Nazhir Airlangga University according to the Waqf Law. This normative research uses statute approach and the conceptual approach. The results show that in practice Nazhir Universitas Airlangga in carrying out his waqf pledge practice does not use AIW un-authentic. That is, Nazhir Airlangga University in carrying out his waqf practice in terms of his pledge deed is in accordance with the procedures in accordance with Law Number 41 of 2004 concerning Waqf.